What is the result of subtracting the second equation from the first? -2x + y = 0 -7x + 3y = 2

Question

What is the result of subtracting the second equation from the first?
-2x + y = 0
-7x + 3y = 2

in progress 0
Mary 1 week 2021-09-12T22:49:47+00:00 2 Answers 0

Answers ( )

    0
    2021-09-12T22:51:09+00:00

    Answer:

    5x – 2y = -2

    Step-by-step explanation:

    -2x – (-7x) = -2x + 7x = 5x

    y – 3y = -2y

    0 – 2 = -2

    0
    2021-09-12T22:51:23+00:00

    Answer:

    5x  -2y = -2

    Step-by-step explanation:

    -2x + y = 0

    -7x + 3y = 2

    Subtract the second equation from the first

    -2x + y = 0

    -(-7x + 3y = 2)

    ————————–

    Distribute the minus sign

    -2x + y = 0

    +7x – 3y = -2

    ————————–

    5x  -2y = -2

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )